PENGUATAN PEMAHAMAN IBU HAMIL TENTANG PENCEGAHAN PENULARAN COVID-19 SELAMA KEHAMILAN - Endah Mulyani; Sulastri Sulastri; Zahrotul Hidayati; Khaulah Mujahidah (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Corona Virus Disease-19 is a contagious infectious disease caused by SARS COV-2, which is often known as the Coronavirus. This disease is new so humans do not have immunity to the virus. Vaccines and drugs for this disease are founds worldwide. Pregnant women are one of the community groups that are prone to contracting COVID-19 because the immune data of pregnant women have decreased due to the process of pregnancy. The rapid survey conducted by many 60% of mothers lacks knowledge about the prevention of transmission of COVID-19 during pregnancy. The considered because pregnant women ask independently to be vigilant in maintaining their health. Based on the above problems, the midwifery study program at the Faculty of Health, University of Muhammadiyah Gresik, will carry out community service activities by strengthening the understanding of pregnant women about how to prevent transmission of COVID-19 during pregnancy. Counseling will provides two methods of approach, namely, the home visit approach and the network approach. Counseling aids used are in the form of videos and pocketbooks. The home visit approach carried out to homemakers who have difficulty in accessing information technology and mothers who do not work. The process in the network makes by spreading the youtube video or video link prepared in a WhatsApp group created by partners. This activity aims to increase maternal understanding of how to prevent transmission of COVID-19 during pregnancy so that pregnant women are healthy and safe.